Wetting behaviour of mixed surfactants on the mild steel surface - Yadav Chandradip Kumar; Subedi Vivek; Mukherjee Monami; Khadka Sita; Karn Anoop; Niraula Tulasi Prasad; Yadav Amar Prasad; Bhattarai Jagadeesh; Bhattarai Ajaya (E3S Web of Conferences)
Interfacial phenomena such as wetting can be enhanced to a greater extent and mixed surfactant systems are promising candidates for the improvement of wettability of hydrophobic surfaces. In this study, the investigation sought to examine the surface-wetting characteristics of mild steel utilizing a blend of the cationic surfactant cetylpyridinium chloride (CPC) and the anionic surfactant sodium dodecyl sulfate (SDS). The wetting behaviour of mild steel surface is quantified in terms of contact angle corresponding to H2SO4, mixed surfactant acid solutions, and methanol for three hours. The contact angles of 0.0008 M, 0.0017 M, and 0.00034 M of mixed surfactant on polished mild steel solution were found to be 38.62°, 39.73°, and 48.50° respectively. The contact angle increases proportionally with the concentration of mixed surfactant in the solution, leading to a visible increase in its hydrophilic nature. On polished mild steel, contact angles of 0%, 10%, 20%, and 30% methanol were measured at 98.21°, 100.39°, 105.29°, and 109.37°, respectively. It shows that the hydrophobic nature increased with an increase in concentration of methanol resulting in less interaction between metal substrate and corrosive species.